2022
DOI: 10.3390/ijms23137361
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Immunological Characterization of Hypermucoviscous Carbapenem-Resistant Klebsiella pneumoniae ST25 Isolates from Northwest Argentina

Abstract: In recent years, an increase in the prevalence hypermucoviscous carbapenem-resistant Klebsiella pneumoniae with sequence type 25 (ST25) was detected in hospitals of Tucuman (Northwest Argentina). In this work, the virulence and the innate immune response to two K. pneumoniae ST25 strains (LABACER 01 and LABACER 27) were evaluated in a murine model after a respiratory challenge. In addition, comparative genomics was performed with K. pneumoniae LABACER01 and LABACER27 to analyze genes associated with virulence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…As in this study, these ST25 isolates showed a K2 capsular serotype linked to increased virulence [2], although no genomic data is available for comparison. Despite two draft genomes of isolates from Argentina proposed to be ST25 were published [51], our analyses indicated that they actually are ST629 and ST551-1LV.…”
Section: Discussionmentioning
confidence: 66%
“…As in this study, these ST25 isolates showed a K2 capsular serotype linked to increased virulence [2], although no genomic data is available for comparison. Despite two draft genomes of isolates from Argentina proposed to be ST25 were published [51], our analyses indicated that they actually are ST629 and ST551-1LV.…”
Section: Discussionmentioning
confidence: 66%
“…In the current study, PCR-based molecular screening for K1 and K2 capsular serotypes revealed that 30% (15/50) of Kp isolates belonged to capsular serotype K2 (harboring wzy gene), with 86.7% (13/15) of the K2 isolates being hmvKp phenotypes, which represent 61.9% of all hmvKp isolates. None of the Kp isolates have been identified as the K1 capsular type attributable to the absence of the magA gene [ 53 , 54 ]. However, it was reported that the magA gene is confined to liver abscesses and linked to hypermucoviscosity and phagocytosis resistance [ 2 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Above all, was shown that K. pneumoniae DY1928 had high dissemination and transfer ability. Animal models are one of the methods to identify the virulence of K. pneumoniae strains (Albarracin et al, 2022). In the mouse experiment, we isolated 11 K. pneumoniae strains that harbored bla NDM-1 homologous to DY1928.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, there are few studies on the transfer and colonization of CRKP from blood to the intestine in mice. Furthermore, there were no studies that characterized the virulence of K. pneumoniae ST25 strains in animal models except the study of Albarracin et al (2022 ). Our findings indicated the high virulence of strain DY1928, together with its resistance to multiple antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%